2010
DOI: 10.1007/s11104-010-0605-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus deficiency is the major limiting factor for wheat on alluvium polluted by the copper mine pyrite tailings: a black box approach

Abstract: Failures of tailings dams have degraded large areas of agricultural alluvial soils worldwide, and concomitant soil pollution studies are abundant. Yet, the data on the actual effects of thereby imposed stresses on major crops are scarce. This work analyses the effect of pyrite tailings from a copper mine, deposited over crop fields by long-term flooding, on wheat (Triticum aestivum L.) under field conditions. The major previously reported polluting agents were Cu, As, Zn, Pb and acidity generated by sulphide o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…The ground particles were then subjected to digestion in a microwave digester, using an HNO 3 -H 2 O 2 acid mixture (2:3 v/v). The content of the macroelements (N, P, K, Ca, Mg) and microelements (Fe, Cu, Mn, Zn, B, and Mo) in the leaves was determined using inductively coupled plasma optical emission spectroscopy according to the method of Nikolic et al (2011) To assess the morphometric fruit properties, a sample of 25 fruits per replication was randomly selected in both harvesting seasons. For average fruit weight, a METTLER balance (±0.01 g accuracy) was used.…”
Section: Plant Growthmentioning
confidence: 99%
“…The ground particles were then subjected to digestion in a microwave digester, using an HNO 3 -H 2 O 2 acid mixture (2:3 v/v). The content of the macroelements (N, P, K, Ca, Mg) and microelements (Fe, Cu, Mn, Zn, B, and Mo) in the leaves was determined using inductively coupled plasma optical emission spectroscopy according to the method of Nikolic et al (2011) To assess the morphometric fruit properties, a sample of 25 fruits per replication was randomly selected in both harvesting seasons. For average fruit weight, a METTLER balance (±0.01 g accuracy) was used.…”
Section: Plant Growthmentioning
confidence: 99%
“…2 ml H 2 O 2 for 2 h. The concentrations of Na, K, Mg and Ca were determined by inductively coupled plasma optical emission (ICP) spectrometry (SpectroGenesis EOP II, Spectro Analytical Instruments GmbH, Kleve, Germany) after diluting the samples with deionised water to a final volume of 25 ml (Nikolić et al 2011).…”
Section: Determination Of K Na Ca and Mgmentioning
confidence: 99%
“…The major process on these polluted soils is oxidative weathering of sulphides, which leads to strong acidification and leaching of most mineral elements (Nikolic and Nikolic 2012). Our previous research showed clear spatial gradients in properties of polluted soils along the transects, <1 km long, perpendicular to the river channel; the concentration of total soil sulphur was a good indicator of pollution load, which regularly decreased with the distance from the river (for more details, see Nikolic et al 2011Nikolic et al , 2014Nikolic and Nikolic 2012).…”
Section: Research Localitymentioning
confidence: 92%